PROFILE OF KAMPUNG UNGGUL BALITNAK CHICKEN GIVEN TURMERIC ESSENCE (Curcuma domestica Val.) IN DRINKING WATER - H., Amirul; Sriyani, N. L. P.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika; Vol 12 No 3 (2024): Vol. 12 No. 3 Tahun 2024; May - June, 2024)
This research aims to determine the effect of giving turmeric essence in drinking water on the carcass profile of Kampung Unggul Balitnak (KUB) chicken. This research was carried 499 out at the Sesetan Teaching Farm, Faculty of Animal Husbandry, Udayana University, Bali for 8 weeks from 08 January – 05 March 2023 using a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications, so there were 20 experimental units. Each unit contains 2 birds of 10 days old and total of 40 KUB chickens used. Treatments consisted of P0 (chickens given drinking water without turmeric essence), P1 (chickens given 1% turmeric essence), P2 (chickens given 2% turmeric essence), P3 (chickens given 3% turmeric essence ). The variables observed were slaughter weight, carcass weight, carcass percentage, meat percentage, bone percentage, and percentage of subcutaneous fat including skin. It was concluded that the carcass profile of KUB chickens given turmeric juice at a level of 2% could increase potdog weight and carcass weight, while giving 1% and 3% turmeric juice gave the same results as the control treatment. The carcass percentage and physical composition of the carcass gave the same results in all treatments.